2021
DOI: 10.3390/nu13062079
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Significance of Fruit and Fruit Products in the Average Polish Diet

Abstract: The aim of the present study was to analyze the supply of energy, 19 nutrients, free sugars, and dietary fiber in the average Polish diet from fruit and fruit products. Our analysis is based on 2016 data from the national representative household budget survey conducted on a sample of 36,886 households, yielding a population of 99,230 individuals. Fruit and fruit products provided 3.12% of energy to the average diet in Poland with the highest share of bananas and apples. The highest significance of this food g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Protein, a so-called building block of life, is a source of amino acids that contain carbon, hydrogen, oxygen, and nitrogen. Fruits in their nature have low proteins content [14]. Globally, most of the studies have highlighted the significant reduction in protein content in all fruits treated with CaC 2 .…”
Section: Implications On Proximate Analysismentioning
confidence: 99%
“…Protein, a so-called building block of life, is a source of amino acids that contain carbon, hydrogen, oxygen, and nitrogen. Fruits in their nature have low proteins content [14]. Globally, most of the studies have highlighted the significant reduction in protein content in all fruits treated with CaC 2 .…”
Section: Implications On Proximate Analysismentioning
confidence: 99%
“…Research into the molecular mechanisms of fruit’s role in health has made some progress. Many studies have confirmed that the soluble fiber, vitamin C, vitamin E, carotenoids, and phytochemicals rich in fruits are significantly associated with anti-oxidation and anti-inflammatory activities, and can also regulate intestinal flora balance [ 12 , 14 , 65 ]. However, very low intakes result in a lack of substantial variation in micronutrient and phytochemical intake.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the availability of seasonal fruits in rural areas. Reports in the literature indicate that limited access to fruit may be influenced by factors such as income, degree of urbanization, level of education, and land use [ 34 ]. Furthermore, lack of knowledge and socioeconomic inequalities may be influencing factors in the consumption of fewer fruits and vegetables than recommended [ 35 ].…”
Section: Discussionmentioning
confidence: 99%